Synovitis in osteoarthritis: the current state of the problem - I. S. Dydykina; E. V. Arutyunova; P. S. Kovalenko; E. V. Nikolaeva; A. V. Naumov (Современная ревматология)
The article presents current data on synovitis (inflammation of the synovial membrane), which is often the only clinical manifestation of osteoarthritis (OA), and considered to be one of the risk factors for the OA development. Synovitis severity correlates with the severity of OA symptoms. The assessment of the prevalence of synovitis presents significant difficulties and depends on the nature and severity of the disease, the cohort in question, diagnostic method, and therapy. The classification based on etiological, clinical and histological characteristics of synovitis is presented. Examination of synovial tissue characteristics and its changes during inflammatory response can significantly expand the possibilities for therapy and prognosis. The use of symptomatic delayed-action drugs (SYSADOA) is considered as the basic treatment of OA. Chondroitin sulfate (Chondroquard®) is one of the well established drugs, it has symptom- and structural-modifying properties. The article presents the results of studies confirming its effectiveness in reducing the severity of knee synovitis.